GI Surgery Annual : Volume 23 - Sahni, Peush; Pal, Sujoy (Springer Singapore : Imprint: Springer, 2017)
The 23rd volume of this highly successful series includes new contemporary topics such as PET in HPBdiseases, short gut syndrome, current status of extended lymphadenectomy in esophageal cancer, splenectomy for haematological disorders, postoperative liver failure, HIPEC, and current issues in surgery of pancreatic cancer. Finally, the chapter on advances in GI surgery, like in each volume in the past, reviews the important new developments in the field. The GI Surgery Annual 23rd Volume provides an overall round up of selected topics that are considered relevant and contemporary by the editors of the series. .
Keywords: Medicine.; Abdominal surgery.; Rectum -- Surgery.; Minimally invasive surgery.; Surgical oncology.; elektronické knihy; electronic books